The Heat Resistant Capabilities of Bioplastic Composites on Sago Hampas Starch-Al2O3 - Amatullah, Afra Najiyah; Kemala, Tetty; Irawadi, Tun Tedja (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
Sago hampas are a waste with a high starch content. The starch from sago hampas can be used as a raw material for bioplastics. However, because bioplastics have a lower heat resistance than conventional plastics, additives are required to increase heat resistance. Aluminum oxide can be used as a metal compound that acts as an additive to increase heat resistance. Bioplastics were created using a weight percentage of 0, 1, 3, and 5% Al2O3. DTA was used to determine the melting point of bioplastics, as well as their mechanical properties, density, and water resistance. The best results were identified using FTIR and SEM. The results showed that adding Al2O3 at 1, 3, and 5% increased the heat resistance of bioplastics with melting points of 270, 274, and 280 oC. Except for mechanical properties, the best results were obtained with a melting point of 280 oC, tensile strength of 3.41 Mpa, elongation of 38.66%, density of 5.52 g cm-3, and 80.28% water resistance for bioplastics with 5% Al2O3 that suitable on Indonesian National Standard 7188.7:2016. The FTIR analysis revealed that bioplastics containing Al2O3 experienced physical interactions. Morphological analysis revealed that Al2O3 was evenly distributed on the bioplastic's surface.